Step * 1 1 1 1 1 1 of Lemma coW-wfdd_functionality

.....wf..... 
1. : 𝕌'
2. A ⟶ Type
3. coW(A;a.B[a])
4. w' coW(A;a.B[a])
5. n:ℕ ⟶ copath(a.B[a];w')
6. ∀i:ℕ
     ((copath-length(p i) i ∈ ℤ (copath-length(p (i 1)) (i 1) ∈ ℤ copathAgree(a.B[a];w';p i;p (i 1)))
7. : ℕ ⟶ copath(a.B[a];w)
8. ∀n:ℕ((∀i:ℕn. (copath-length(q i) i ∈ ℤ))  (∀i:ℕ1. copathAgree(a.B[a];w;q i;q (i 1))))
9. ∀n:ℕ
     ((∀i:ℕn. (copath-length(p i) i ∈ ℤ))
      (∀i:ℕn. ((copath-length(q i) i ∈ ℤ) ∧ coW-equiv(a.B[a];copath-at(w;q i);copath-at(w';p i)))))
⊢ λn.if bdd-all(n 1;i.(copath-length(q i) =z i)) then else () fi  ∈ {p:n:ℕ ⟶ copath(a.B[a];w)| 
                                                                           ∀i:ℕ
                                                                             ((copath-length(p i) i ∈ ℤ)
                                                                              (copath-length(p (i 1)) (i 1) ∈ ℤ)
                                                                              copathAgree(a.B[a];w;p i;p (i 1)))} 
BY
(((MemTypeCD THEN Auto) THEN Reduce 0) THEN RepeatFor (AutoSplit)) }

1
1. : 𝕌'
2. A ⟶ Type
3. coW(A;a.B[a])
4. w' coW(A;a.B[a])
5. n:ℕ ⟶ copath(a.B[a];w')
6. ∀i:ℕ
     ((copath-length(p i) i ∈ ℤ (copath-length(p (i 1)) (i 1) ∈ ℤ copathAgree(a.B[a];w';p i;p (i 1)))
7. : ℕ ⟶ copath(a.B[a];w)
8. ∀n:ℕ((∀i:ℕn. (copath-length(q i) i ∈ ℤ))  (∀i:ℕ1. copathAgree(a.B[a];w;q i;q (i 1))))
9. ∀n:ℕ
     ((∀i:ℕn. (copath-length(p i) i ∈ ℤ))
      (∀i:ℕn. ((copath-length(q i) i ∈ ℤ) ∧ coW-equiv(a.B[a];copath-at(w;q i);copath-at(w';p i)))))
10. : ℕ
11. copath-length((λn.if bdd-all(n 1;i.(copath-length(q i) =z i)) then else () fi i) i ∈ ℤ
12. copath-length((λn.if bdd-all(n 1;i.(copath-length(q i) =z i)) then else () fi (i 1)) (i 1) ∈ ℤ
13. ↑bdd-all(i 1;i.(copath-length(q i) =z i))
14. ↑bdd-all((i 1) 1;i.(copath-length(q i) =z i))
⊢ copathAgree(a.B[a];w;q i;q (i 1))


Latex:


Latex:
.....wf..... 
1.  A  :  \mBbbU{}'
2.  B  :  A  {}\mrightarrow{}  Type
3.  w  :  coW(A;a.B[a])
4.  w'  :  coW(A;a.B[a])
5.  p  :  n:\mBbbN{}  {}\mrightarrow{}  copath(a.B[a];w')
6.  \mforall{}i:\mBbbN{}
          ((copath-length(p  i)  =  i)
          {}\mRightarrow{}  (copath-length(p  (i  +  1))  =  (i  +  1))
          {}\mRightarrow{}  copathAgree(a.B[a];w';p  i;p  (i  +  1)))
7.  q  :  \mBbbN{}  {}\mrightarrow{}  copath(a.B[a];w)
8.  \mforall{}n:\mBbbN{}.  ((\mforall{}i:\mBbbN{}n.  (copath-length(q  i)  =  i))  {}\mRightarrow{}  (\mforall{}i:\mBbbN{}n  -  1.  copathAgree(a.B[a];w;q  i;q  (i  +  1))))
9.  \mforall{}n:\mBbbN{}
          ((\mforall{}i:\mBbbN{}n.  (copath-length(p  i)  =  i))
          {}\mRightarrow{}  (\mforall{}i:\mBbbN{}n.  ((copath-length(q  i)  =  i)  \mwedge{}  coW-equiv(a.B[a];copath-at(w;q  i);copath-at(w';p  i)))))
\mvdash{}  \mlambda{}n.if  bdd-all(n  +  1;i.(copath-length(q  i)  =\msubz{}  i))  then  q  n  else  ()  fi 
    \mmember{}  \{p:n:\mBbbN{}  {}\mrightarrow{}  copath(a.B[a];w)| 
          \mforall{}i:\mBbbN{}
              ((copath-length(p  i)  =  i)
              {}\mRightarrow{}  (copath-length(p  (i  +  1))  =  (i  +  1))
              {}\mRightarrow{}  copathAgree(a.B[a];w;p  i;p  (i  +  1)))\} 


By


Latex:
(((MemTypeCD  THEN  Auto)  THEN  Reduce  0)  THEN  RepeatFor  2  (AutoSplit))




Home Index